John Dryden : a survey and bibliography of critical studies, 1895-1974 - Latt, David J. (University of Minnesota Press, 1976)
This annotated bibliography represents a comprehensive updating of Samuel Holt Monk?s earlier work, also published by the University of Minnesota Press, John Dryden: A List of Critical Studies Published from 1895 to 1948 (out of print). Since the publicat.